Directive Illocutionary Acts in Progressive Relaxation - Nurhadi, Jatmika; Fauzy, Eka Rahmat; Khotima, Nurul Ashyfa; Rahman, Sintia Hapsyah (Universitas Muhammadiyah Malang, 2024)
Hypnotherapy has become a widely utilized method in medical procedures, not only for reducing pain and emotional stress but also for enhancing recovery, reducing procedure time, and stabilizing physiological parameters. Language plays a pivotal role in hypnotherapy, particularly in the context of directive illocutionary acts, influencing individuals to attain relaxation. This research aims to identify and analyze directive illocutionary acts within scripts of progressive relaxation hypnotherapy and determine the dominant types and functions of speech acts. Employing a qualitative methodology, data were collected from the Indonesian Board of Hypnotherapy (IBH) Hypnotherapy Module. Data on speech acts were analyzed using the enactive model and the Directness Scale. The dominant directive illocutionary acts were identified as Focusing, Commanding, and Calming. This study provides insights into how language influences individuals in achieving relaxation during hypnotherapy. Based on the research findings, it is concluded that Focusing, Commanding, and Calming speech acts play a crucial role in guiding individuals into a trance state during the hypnosis process.